2017
DOI: 10.1063/1.4993425
|View full text |Cite
|
Sign up to set email alerts
|

Low surface damage dry etched black silicon

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
18
1
1
Order By: Relevance
“…In order to capitalize on the superior optical properties of b‐Si, surface recombination must therefore be reduced to levels similar to those measured on competing texturing technologies. Recently, b‐Si surfaces characterized by lower recombination rates have been fabricated by decreasing the capacitively coupled power (CCP) during plasma processing, leading to a lower kinetic energy of ions and thus reduced surface damage, as confirmed by high‐resolution transmission electron microscopy characterization of individual nanostructures . However, that process still required a certain amount of CCP and etching time ≥10 min to reach the desired antireflective properties, which is not convenient in view of process scalability.…”
contrasting
confidence: 76%
“…In order to capitalize on the superior optical properties of b‐Si, surface recombination must therefore be reduced to levels similar to those measured on competing texturing technologies. Recently, b‐Si surfaces characterized by lower recombination rates have been fabricated by decreasing the capacitively coupled power (CCP) during plasma processing, leading to a lower kinetic energy of ions and thus reduced surface damage, as confirmed by high‐resolution transmission electron microscopy characterization of individual nanostructures . However, that process still required a certain amount of CCP and etching time ≥10 min to reach the desired antireflective properties, which is not convenient in view of process scalability.…”
contrasting
confidence: 76%
“…Interestingly, Mews et al reported a higher Jsc loss in the visible and a lower loss in the IR as compared to our results, which may be connected to difference in the characteristic shape and size of bSi. In our case, the loss in the IR is due to poor light trapping of the bSi caused by the relatively small characteristic size and by the shape of the nanostructures, as discussed in [11]. While texturing both sides of the cell might ameliorate this issue, further work on the RIE is needed to produce structures with more appropriate shape and even lower additional surface damage.…”
Section: Resultsmentioning
confidence: 88%
“…2 . Firstly, random etching of the native oxide (ions and oxygen) roughens the surface because of the forming of micro-mask [ 26 , 28 ]. Then the lateral etching of microstructures on the substrate surface is inhibited by controlling the composition of etching gas and using the passivation of some products during etching [ 26 ], and the nanostructures on the substrate surface are obtained, namely the final black GaAs surface, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%